Performance analysis of local government websites – Minsk and Siedlce County - Kowalczyk, Marcin (Management and Administration Journal, 2023)
The paper shows the characteristics of the information society in using of the Internet. The article presents how companies and households use the e-government. The analysis of websites of local governments in Mazowieckie: Siedlce and Minsk County was realized. It was examined theperformance: size and loading time of websites.